Mindset Moderates Healthcare Providers' Longitudinal Performance in a Digital Neonatal Resuscitation Simulator - Lu, Chang; Ghoman, Simran K.; Cutumisu, Maria; Schmölzer, Georg M. (Frontiers in Pediatrics, 2021)
Background Simulation education can benefit healthcare providers (HCPs) by providing opportunities to practice complex neonatal-resuscitation tasks in low-stakes environments. To our knowledge, no study investigated the role of growth mindset on longitudinal performance on neonatal resuscitation before and after simulation-based training. Objective This study examines whether 1) the RETAIN digital/table-top simulators facilitate HCPs’ neonatal resuscitation knowledge gain, retention, and transfer; and 2) growth mindset moderates HCPs’ longitudinal performance in neonatal resuscitation. Methods Participants were n=50 HCPs in a tertiary perinatal centre in Edmonton, Canada. This longitudinal study was conducted in three stages including: 1) a pre-test and a mindset survey, immediately followed by a post-test using the RETAIN digital simulator from April to August 2019; 2) a two-month delayed post-test using the same RETAIN neonatal resuscitation digital simulator from June to October 2019; and 3) a five-month delayed post-test using the low-fidelity table-top neonatal resuscitation digital simulator from September 2019 to January 2020. Three General Linear Mixed Model (GLMM) repeated-measures analyses investigated HCPs’ performance on neonatal resuscitation over time and the moderating effect of growth mindset on the association between test time points and task performance. Results Compared with their pre-test performance, HCPs effectively improved their neonatal resuscitation knowledge after the RETAIN digital simulation-based training on the immediate post-test (Est=1.88, p<.05), retained their knowledge on the two-month delayed post-test (Est=1.36, p<.05), and transferred their knowledge to the table-top simulator after five months (Est=2.01, p<.05). Although growth mindset did not moderate the performance gain from the pre-test to the immediate post-test, it moderated the relationship between HCPs’ pre-test and long-term knowledge retention (i.e., the interaction effect of mindset and the two-month post-test was significant: Est=0.97, p<.05). The more they endorsed a growth mindset, the better the HCPs performed on the post-test, but only when they were tested after two months. Conclusions Digital simulators for neonatal resuscitation training can effectively facilitate HCPs’ knowledge gain, maintenance, and transfer. Besides, growth mindset shows a positive moderating effect on the longitudinal performance improvement in simulation-based training. Future research can be conducted to implement growth-mindset interventions promoting more effective delivery of technology-enhanced, simulation-based training and assessment.